Prediction of building energy consumption by using artificial neural networks - Ekici, Betul Bektas; Aksoy, U. Teoman (Elsevier Sci Ltd, 2009)
In this study, the main objective is to predict buildings energy needs benefitting from orientation, insulation thickness and transparency ratio by using artificial neural networks. A backpropagation neural network has been preferred and the data have been presented to network by being normalized. The numerical applications were carried out with finite difference approach for brick walls with and without insulation of transient state one-dimensional heat conduction. Three different building samples with different form factors (FF) were selected. For each building samples 0-2.5-5-10-15 cm insulations are assumed to be applied. Orientation angles of the samples varied from 0 degrees to 80 degrees and the transparency ratios were chosen as 15-20-25%. A computer program written in FORTRAN was used for the calculations of energy demand and ANN toolbox of MATLAB is used for predictions. As a conclusion; when the calculated values compared with the outputs of the network, it is proven that ANN gives satisfactory results with deviation of 3.43% and successful prediction rate of 94.8-98.5%. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ANN; Heating energy prediction; Insulation; Orientation